Case Report: Hypocomplementemic urticarial vasculitis syndrome in a pediatric patient with complement factor 1 deficiency - Lin, Sallie; Kafisheh, Dina; Elder, Melissa E. (Frontiers in Pediatrics, 2024)
Urticarial vasculitis (UV) is a type III hypersensitivity reaction, characterized by immune complex deposition in small vessels leading to complement activation. Hypocomplementemic urticarial vasculitis syndrome (HUVS) represents the most severe form of UV, manifesting as chronic and recurrent urticarial skin lesions with leukocytoclastic vasculitis on histology, hypocomplementemia, anti-C1q antibodies, and systemic organ involvement. This case study focuses on an adolescent who initially presented with invasive pneumococcal infection and was later diagnosed with two rare disorders: HUVS and coexisting complement factor 1 (CF1) deficiency by genotyping. The role of CF1 deficiency in the development of HUVS in this patient is uncertain but has not previously been described.